In situ X-ray diffraction study of deformation and shape recovery in the aged U–6.2wt%Nb alloy. Issue 2 (30th January 2017) - Zhang, Y. Z.; Wang, D. P.; Guan, W. J.; Chen, X. L.; Wang, X. L.
Abstract : The present work focuses on the deformation and recovery mechanisms of aged monoclinic U–Nb alloy under tension and load–unload cycle testing using in situ X-ray diffraction (XRD). The U–6.2wt% Nb (U–6.2Nb) alloy was prepared and aged at 200 °C, and then underwent tensile testing followed by the in situ XRD. The experimental results indicate that the change of diffraction peaks can serve to accurately characterize the macroscopic deformation and recovery. Compared with the as-quenched alloy, the aged U–6.2Nb alloy displays different behavior during deformation and subsequent recovery. Phase transformation competes with twin rearrangement to dominate the deformation and recovery between elastic stage and slip stage of the alloy. The lattice plane relationship between α″ and γ° during phase transformation has also been given.